Albert Watkins and Howard Watkins Family Genealogy Trip to Tennessee - Watkins, Howard::::::::: (1986)
William Bravel Watkins and wife, Sarah Ann Prince Watkins; parents of Estelle Watkins Morgan Sarah and William Watkins are paternal grandparents of William Riley Watkins, former District Rep for Assemblymember Jim Costa